Acoustic design and analyses of a double Skin Façade system. (February 2021) - Hu, Zhongyu; Maxit, Laurent; Cheng, Li
Abstract: Noise insulation in buildings is an important topic in building acoustics. Existing literature shows a clear lack of simulation tools for the design, analysis, and assessment of the sound insulation performance of building structures, especially when the frequency of interest becomes higher. To tackle this problem, a numerical based Condensed Transfer Function (CTF) method, alongside a piecewise calculation scheme, is adapted to investigate a simplified Double Skin Façade (DSF) system. Embracing a sub-structuring philosophy, the method offers an appealing alternative to existing analyses ones in terms of providing enhanced computational efficiency and enriched physical description of the system. Numerical analyses reveal dominant sound transmission paths into a typical receiving room. Meanwhile, as sound reduction devices, microperforated panels are investigated in two arrangements, triggering different sound absorption behaviors and design principles. The proposed model allows extensions to other building structures.